Combination systemic therapies with immune checkpoint inhibitors in pancreatic cancer: overcoming resistance to single‐agent checkpoint blockade. Issue 1 (8th October 2018) - Gong, Jun; Hendifar, Andrew; Tuli, Richard; Chuang, Jeremy; Cho, May; Chung, Vincent; Li, Daneng; Salgia, Ravi
Abstract: Immune checkpoint inhibitors have demonstrated broad single‐agent antitumor activity and a favorable safety profile that render them attractive agents to combine with other systemic anticancer therapies. Pancreatic cancer has been fairly resistant to monotherapy blockade of programmed cell death protein 1 receptor, programmed death ligand 1, and cytotoxic T‐lymphocyte associated protein 4. However, there is a growing body of preclinical evidence to support the rational combination of checkpoint inhibitors and various systemic therapies in pancreatic cancer. Furthermore, early clinical evidence has begun to support the feasibility and efficacy of checkpoint inhibitor‐based combination therapy in advanced pancreatic cancer. Despite accumulating preclinical and clinical data, there remains several questions as to the optimal dosing and timing of administration of respective agents, toxicity of combination strategies, and mechanisms by which immune resistance to single‐agent checkpoint blockade are overcome. Further development of biomarkers is also important in the advancement of combination systemic therapies incorporating checkpoint blockade in pancreatic cancer. Results from an impressive number of ongoing prospective clinical trials are eagerly anticipated and will seek to validate the viability of combination immuno‐oncology strategies in pancreatic cancer.